Top ten most cited papers published in IJABE according to Google scholar - Yingkuan, Wang (International Journal of Agricultural and Biological Engineering, 2013)
1. Overview of biomass pretreatment for cellulosic ethanol productionYi Zheng, Zhongli Pan, Ruihong ZhangInt J Agric & Biol Eng, 2009; 2(3) Cited times: 1062. Current status of adoption of no-till farming in the world and some of its main benefitsRolf Derpsch, Theodor Friedrich, Amir Kassam, Li HongwenInt J Agric & Biol Eng, 2010; 3(1) Cited times: 493. Effect of nitrogen and extraction method on algae lipid yield Ying Shen, Zhijian Pei, Wenqiao Yuan, Enrong MaoInt J Agric & Biol Eng, 2009; 2(1) Cited times: 254. Size matters: small distributed biomass energy production systems for economic viabilityRoger Ruan, Paul Chen, Richard Hemmingsen, Vance Morey, Doug TiffanyInt J Agric & Biol Eng, 2008; 1(1)Cited times: 125. Mathematical modeling of microwave- assisted convective heating and drying of grapesGokhan Bingol, Zhongli Pan, John S.Robert, Y. Onur Devres, Murat O.BalabanInt J Agric & Biol Eng, 2008; 1(2)Cited times: 106. Nondestructive assessment of quality of Nanfeng mandarin fruit by a portable near infrared spectroscopySun Xudong, Zhang Hailiang, Liu YandeInt J Agric & Biol Eng, 2009; 2(1) Cited times: 107. Optimization of Japanese beech hydrolysis treated with batch hot-compressed water by response surface methodologyL